A Multilevel Structural Equation Model for the Interrelationships Between Multiple Latent Dimensions of Childhood Socio-Economic Circumstances, Partnership Transitions and Mid-Life Health. (25th February 2020) - Zhu, Yajing; Steele, Fiona; Moustaki, Irini
Summary: We propose a multilevel structural equation model to investigate the interrelationships between childhood socio-economic circumstances, partnership formation and stability, and mid-life health, using data from the 1958 British birth cohort. The structural equation model comprises latent class models that characterize the patterns of change in four dimensions of childhood socio-economic circumstances and a joint regression model that relates these categorical latent variables to partnership transitions in adulthood and mid-life health, while allowing for informative dropout. The model can be extended to handle multiple outcomes of mixed types and at different levels in a hierarchical data structure.